The firm-level and regional determinants of FDI distribution in Poland: Does sector of economy matter? - Ablov, Artur (Economics of the 21st Century, 2015)
This article examines the firm-level and regional determinants of inward FDI into Polish firms in the framework of sectoral analysis. All Polish companies with foreign capital (21 895 firms) were divided into three basic groups: firms of manufacturing sector (11 064 firms), services (6718) and sales (4149). This investigation includes the period from 2003 to 2012 (10 years). The main aim of this article is to determine what factors (firm-level or regional) have more impact on FDI attraction and how their impact depends on a sector which a host firm operates in. The firm-level characteristics which were used in this analysis were total assets of a host firm, its productivity, firm size, R&D expenditure, level of high-skilled workers and age of a recipient firm. The regional determinants of inward FDI into Polish firms were: the economic potential of a region in which a firm operates, the road and rail road density of this region and the location of a firm: closer to EU or non-EU countries and closer to seaside or to the capital city – Warsaw
Ekonomia XXI Wieku = Economics of the 21st Century, 2015, Nr 4 (8), s. 74-98
Keywords: foreign direct investment; firm-level characteristics; regional determinant; location choice; Polish firms; bezpośrednie inwestycje zagraniczne; wewnątrzfirmowe determinanty; regionalne determinanty; wybór lokalizacji; polskie przedsiębiorstwa